2016
DOI: 10.1186/s12889-016-2844-0
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of unhealthy behaviors, the prevalence and receipt of antiviral treatment for disabled adult hepatitis B and C carriers

Abstract: BackgroundEvidence indicates that hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are the leading causes of liver cirrhosis and hepatocellular carcinoma. Antiviral treatments have recently been reported as successful cures. However, the prevalence rates of HBV or HCV infection, unhealthy behaviors and receipt of adequate treatment in disabled adults have not been described. The aim of this study was to examine the prevalence of HBV or HCV carriers, receipt of antiviral treatment, and early detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
1
4
0
4
Order By: Relevance
“…Additionally, many participants were smoking, drinking alcohol, and chewing betel nuts while receiving AVT. The participants' characteristics support the findings of previous studies that most patients with HCV are from a low socioeconomic status and, thus, have poor oral hygiene behaviours (Chang et al, 2015;Jane et al, 2016). The present finding echoed previous studies that men adopt less oral Note.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, many participants were smoking, drinking alcohol, and chewing betel nuts while receiving AVT. The participants' characteristics support the findings of previous studies that most patients with HCV are from a low socioeconomic status and, thus, have poor oral hygiene behaviours (Chang et al, 2015;Jane et al, 2016). The present finding echoed previous studies that men adopt less oral Note.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have indicated that most hepatitis C patients have low socioeconomic backgrounds, which could explain why they have more oral health problems compared with healthy people (Coates et al, 2000;Hayashi et al, 2013;Jane, Chiu, Chen, Lin, & Chen, 2016) and this, in turn, increases their tendency to drop out of the AVT, which lasts for 24-48 weeks (Hepgul et al, 2012;Nagao et al, 2012;Saito et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…의과 연구의 경우 단면조사연구가 1편 30) , 비무작위대 조 임상연구 1편 31) , 단일군 전후비교 연구가 2편 32,33) , 후 향적 차트 리뷰 2편 34,35) 이 보고되었다. 증례보고가 1편 36) , 기타 단순 보고서나 문헌고찰이 4편 [37][38][39][40] 이 보고되었다 (Table II).…”
unclassified
“…(2) 연구자 선정된 연구들에서 13편의 연구가 치과 치료 관련 연 구 [17][18][19][20][21][22][23][24][25][26][27][28][29] 였으며, 나머지 11편은 모두 의과 치료 관련 연구 [30][31][32][33][34][35][36][37][38][39][40] 이었다( Table II).…”
unclassified
See 1 more Smart Citation